2022
DOI: 10.3390/app12157612
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Magnetic Flux Density under Stress and Its Application in Nondestructive Testing

Abstract: Carbon steels are commonly used in railroad, shipment, building, and bridge construction. They provide excellent ductility and toughness when exposed to external stresses. They are able to resist stresses and strains effectively, and guarantee safe operation of the devices through nondestructive testing (NDT). The magnetic metal memory (MMM) can be used as an NDT method to measure the residual stress. The ability of carbon steel to produce a magnetic memory effect under stress is explored here, and enables the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Previous studies have indicated that residual stresses and stress concentrations can have an impact on mechanical properties, erosion resistance, dimensional precision, fatigue damage resistance, and structural life [8,10]. In papers [11,12], it was proven that residual stress affects the magnetic properties of ferromagnetic materials.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that residual stresses and stress concentrations can have an impact on mechanical properties, erosion resistance, dimensional precision, fatigue damage resistance, and structural life [8,10]. In papers [11,12], it was proven that residual stress affects the magnetic properties of ferromagnetic materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to apply it to very narrow cracks, such as fatigue cracks. In addition, the change in the magnetic flux density (MFD) with the change in stress remains unclear, where conventional studies on MMM states that the magnetic flux density changes when stress changes or fatigue cracks occur, even when no external magnetic field is applied [32][33][34][35][36]. Therefore, it is uncoherent to use a magnetic dipole that assumes that an external magnetic field is applied which make the specimen in a magnetized state.…”
Section: Introductionmentioning
confidence: 99%
“…This is because of the magnetic field distribution in the stress region, which is related to the magnetic field distribution generated in the sample after the stress is released, and the pattern was confirmed experimentally. On the other hand, Berkache et al [33] compared the stress analysis using the finite element method (FEM), measured the 3-axial magnetic flux density distribution, and examined the correlation. The stress distribution, which uses the parameter of the 3-axial magnetic flux density, was set as a qualitative relationship in the third polynomial formula.…”
Section: Introductionmentioning
confidence: 99%